A new species of arboreal Rhinella (Anura: Bufonidae) from Yanachaga-Chemillén National Park in central Peru - Lehr, Edgar; Pramuk, Jennifer B.; Hedges, S. Blair; Córdova, Jesús H. (Zootaxa, 2007)
A new arboreal species of Rhinella tentatively assigned to the veraguensis Group is described from the National Park Yanachaga Chemillén at 2600 m elevation in central Peru (Departamento de Pasco).The new species is characterized by a maximum snout-vent length of 45.7 mm, a moderate body with relatively long and slim extremities, a dorsum with small tubercles and enlarged tubercles on legs, a distinct tympanum, distinct vertical keel on snout, weak orbitotympanic and postorbital crests, weakly defined row of dorsolateral tubercles, and males with vocal slits, nuptial pads, hypertrophied arms, and a protuberant, ventrally oriented cloaca. The new species is compared with other members of the veraguensis Group and is considered most similar to arboreal R. tacana from northern Bolivia. The skull of the new species is described and compared to other members of the veraguensis Group. Tadpole and call of the new species remain unknown.